Oxidative stress and nitric oxide are increased in obese children and correlate with cardiometabolic risk and renal function - Correia-Costa, Liane; Sousa, Teresa; Morato, Manuela; Cosme, Dina; Afonso, Joana; Areias, José C.; Schaefer, Franz; Guerra, António; Afonso, Alberto C.; Azevedo, Ana; Albino-Teixeira, António (British journal of nutrition, 2016)
Oxidative stress and nitric oxide (NO) appear to represent important links between obesity and cardiovascular, metabolic and/or renal disease. We investigated whether oxidative stress and NO production/metabolism are increased in overweight and obese prepubertal children and correlate with cardiometabolic risk and renal function. We performed a cross-sectional evaluation of 313 children aged 8-9 years. Anthropometrics, 24-h ambulatory blood pressure, pulse wave velocity (PWV), insulin resistance (homoeostasis model assessment index (HOMA-IR)), inflammatory/metabolic biomarkers, estimated glomerular filtration rate (eGFR), plasma total antioxidant status (TAS), plasma and urinary isoprostanes (P-Isop, U-Isop), urinary hydrogen peroxide (U-H2O2), and plasma and urinary nitrates and nitrites (P-NOx, U-NOx) were compared among normal weight, overweight and obese groups, according to WHO BMI z-score reference. U-Isop were increased in the obese group, whereas U-NOx were increased in both overweight and obese children. U-Isop were positively correlated with U-H2O2, myeloperoxidase (MPO), high-sensitivity C-reactive protein, HOMA-IR and TAG. TAS correlated negatively with U-Isop and MPO and positively with PWV. HOMA-IR and U-H2O2 were associated with higher U-Isop, independently of BMI and eGFR, and total cholesterol and U-H2O2 were associated with U-NOx, independently of BMI, eGFR values and P-NOx concentration. In overweight and obese children, eGFR decreased across P-NOx tertiles (median: 139·3 (25th, 75th percentile 128·0, 146·5), 128·0 (25th, 75th percentile 121·5, 140·4), 129·5 (25th, 75th percentile 119·4, 138·3), P - for linear trend=0·003). We conclude that oxidant status and NO are increased in relation to fat accumulation and, even in young children, they translate into higher values of cardiometabolic risk markers and affect renal function.
Gesehen am 05.05.2020